High Ambient Temperature Aggravates Experimental Autoimmune Uveitis Symptoms - Pan, Su; Tan, Handan; Chang, Rui; Wang, Qingfeng; Zhu, Ying; Chen, Lin; Li, Hongxi; Su, Guannan; Zhou, Chunjiang; Cao, Qingfeng; Kijlstra, Aize; Yang, Peizeng (Frontiers in Cell and Developmental Biology, 2021)
Whether ambient temperature influences immune responses leading to uveitis is unknown. We thus tested whether ambient temperature affects the symptoms of experimental autoimmune uveitis (EAU) in mice and investigated possible mechanisms. C57BL/6 mice were kept at a normal (22 °C) or high temperature (30 °C) housing conditions for 2 weeks and were then immunized with human interphotoreceptor retinoid-binding protein (IRBP651–670) peptide to induce EAU. Histological changes were monitored to evaluate the severity of uveitis. Frequency of Th1 cells and Th17 cells was measured by flow cytometry (FCM). The expression of IFN-γ and IL-17A mRNA was measured by real-time PCR. The generation of neutrophil extracellular traps (NETs) was quantified by enzyme-linked immunosorbent assay (ELISA). Differential metabolites in the plasma of the mice kept in the aforementioned 2 ambient temperatures were measured via ultra-high-performance liquid chromatography triple quadrupole mass spectrometry quadrupole time of flight mass spectrometry (UHPLC-QQQ/MS). The differential metabolites identified were used to evaluate their effects on differentiation of Th1 and Th17 cells and generation of NETs in vitro. The results showed that EAU mice kept at high temperature experienced a more severe histopathological manifestation of uveitis than mice kept at a normal temperature. A significantly increased frequency of Th1 and Th17 cells in association with an upregulated expression of IFN-γ and IL-17A mRNA was observed in the splenic lymphocytes and retinas of EAU mice in high temperature. The expression of NETs as evidenced by myeloperoxidase (MPO) and neutrophil elastase (NE), was significantly el-evated in serum and supernatants of neutrophils from EAU mice kept at high temperature compared to the normal temperature group. The metabolites in the plasma from EAU mice, fumaric acid and succinic acid, were markedly increased in the high temperature group and could induce the generation of NETs via the NADPH oxidase-dependent pathway, but did not influence the frequency of Th1 and Th17 cells. Our findings suggest that an increased ambient temperature is a risk factor for the development of uveitis. This is associated with the induction of Th1 and Th17 cells as well as the generation of NETs which could be mediated by the NADPH oxidase-dependent pathway.